Unravelling Checkpoint Inhibitor Associated Autoimmune Diabetes: From Bench to Bedside - Wu, Linda; Tsang, Venessa H. M.; Sasson, Sarah C.; Menzies, Alexander M.; Carlino, Matteo S.; Brown, David A.; Clifton-Bligh, Roderick; Gunton, Jenny E. (Frontiers in Endocrinology, 2021)
Immune checkpoint inhibitors have transformed the landscape of oncological therapy, but at the price of a new array of immune related adverse events. Among these is β-cell failure, leading to checkpoint inhibitor-related autoimmune diabetes (CIADM) which entails substantial long-term morbidity. As our understanding of this novel disease grows, parallels and differences between CIADM and classic type 1 diabetes (T1D) may provide insights into the development of diabetes and identify novel potential therapeutic strategies. In this review, we outline the knowledge across the disciplines of endocrinology, oncology and immunology regarding the pathogenesis of CIADM and identify possible management strategies.